Simulation and Modeling Application in Agricultural Mechanization. (20th September 2012) - Hudzari, R. M.; Ssomad, M. A. H. A.; Syazili, R.; Fauzan, M. Z. M.
Abstract : This experiment was conducted to determine the equations relating the Hue digital values of the fruits surface of the oil palm with maturity stage of the fruit in plantation. The FFB images were zoomed and captured using Nikon digital camera, and the calculation of Hue was determined using the highest frequency of the value for R, G, and B color components from histogram analysis software. New procedure in monitoring the image pixel value for oil palm fruit color surface in real-time growth maturity was developed. The estimation of day harvesting prediction was calculated based on developed model of relationships for Hue values with mesocarp oil content. The simulation model is regressed and predicts the day of harvesting or a number of days before harvest of FFB. The result from experimenting on mesocarp oil content can be used for real-time oil content determination of MPOB color meter. The graph to determine the day of harvesting the FFB was presented in this research. The oil was found to start developing in mesocarp fruit at 65 days before fruit at ripe maturity stage of 75% oil to dry mesocarp.